Numerical simulation on movement behavior of dispersed phase droplets of water-in-oil emulsion under electric field - HUANG Ya'nan; HOU Lei; XIAO Kaixi; LI Yanhao; ZHANG Rui; CHAI Chong (You-qi chuyun, 2022)
To explore the demulsification mechanism of emulsion under electric fields, the movement process of dispersed phase droplets in water-in-oil emulsion was simulated with the finite element method. Herein, the oil-water distribution was represented with the phase field method, and the accuracy and efficiency of calculation on fluid flow process was improved with the structured quadrilateral grid. Besides, the influence laws of electric field parameters, as well as the physical parameters of emulsion, on the droplet deformation and coalescence were systematically studied to provide theoretical basis for the efficient application of electric demulsification technology. According to the results, the higher the electric field intensity, root mean square(RMS) of electric field waveform and droplet size, the greater the deformability and coalescence ability of droplets are. The droplet deformation is independent of frequency under the high-frequency conditions, and the frequency has little effect on the coalescence rate of droplets. Meanwhile, the droplet deformation and coalescence rate can been improved by decreasing the continuous phase viscosity and oil-water interfacial tension. In addition, the microcosmic mechanism of droplet deformation and coalescence was also discussed. It is found that the maximum droplet deformation is in strong linear relationship with the electric Weber number in the case of small deformation, and the electric field intensity,droplet size and interfacial tension affect the coalescence efficiency of droplets by influencing the evolution of liquid bridge between droplets.